2016
DOI: 10.2147/dmso.s97623
|View full text |Cite
|
Sign up to set email alerts
|

Depression in diabetic patients attending University of Gondar Hospital Diabetic Clinic, Northwest Ethiopia

Abstract: BackgroundDiabetes mellitus, frequently associated with comorbid depression, contributes to the double burden of individual patients and community. Depression remains undiagnosed in as many as 50%–75% of diabetes cases. This study aimed to determine the prevalence and associated factors of depression among diabetic patients attending the University of Gondar Hospital Diabetic Clinic, Northwest Ethiopia.MethodsAn institution-based cross-sectional study was conducted from March to May 2014 among 422 sampled diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…This finding is comparable with studies conducted in Peru (11.2%) [ 19 ] and the USA (8.3%) [ 7 ]. However, this result is lower than studies conducted in Ethiopia (15.4 to 64.9%) [ 9 15 ], Tanzania (30%) [ 29 ], Nigeria (30%) [ 30 ], Uganda (34.8%) [ 31 ], Sudan (44%) [ 32 ], Pakistan (14.7%) [ 33 ], and Iran (71.8%) [ 8 ]. The possible explanation for these differences might be due to the types of diagnostic tools used to assess depression and its respective cut of value used to decide depression has occurred.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…This finding is comparable with studies conducted in Peru (11.2%) [ 19 ] and the USA (8.3%) [ 7 ]. However, this result is lower than studies conducted in Ethiopia (15.4 to 64.9%) [ 9 15 ], Tanzania (30%) [ 29 ], Nigeria (30%) [ 30 ], Uganda (34.8%) [ 31 ], Sudan (44%) [ 32 ], Pakistan (14.7%) [ 33 ], and Iran (71.8%) [ 8 ]. The possible explanation for these differences might be due to the types of diagnostic tools used to assess depression and its respective cut of value used to decide depression has occurred.…”
Section: Discussionmentioning
confidence: 72%
“…Prevalence of depression among DM patients varies across countries with 8.3% % in the USA [ 7 ] to 71.8% in Iran [ 8 ], and in Ethiopia, it is ranging from 15.4 to 64.9% [ 9 15 ] with 39.73% pooled prevalence [ 16 ]. The presence of depression among diabetic patients increases the noncompliance to the medical treatment, decreases the quality of life, increases the risk of complication, results in poor prognosis, and increases mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of depression in people with diabetes mellitus is about two to three times higher compared to the general population [11][12][13]. Studies have reported varying results on the prevalence of depression in diabetes patients that ranges from 5.9% to 87% [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of depression in T2D patient was 5.5–49.6% [10, 1422]. Even though most studies was on Western samples, there have been emerging studies in developing countries including Ethiopia [16, 23–25]. A cross-sectional study by Erkie et al described depression was diagnosed in 64.8% of T2D outpatient [23].…”
Section: Introductionmentioning
confidence: 99%